(untitled) (Research, Society and Development, 2022)
Cowpea (Vigna unguiculata L.) is a legume with low yield in the Amapá state, related to inadequate nutritional management, and cultivation can be optimized by inoculating the seeds with nitrogen-fixing bacteria. Thus, the objective was to evaluate the growth and production of cowpea inoculated with Bradyrhizobium japonicum associated with nitrogen fertilization cultivated in forest soil in the municipality of Mazagão, state of Amapá. The experiment was carried out at the Federal University of Amapá, with a completely randomized design, with eight treatments, three replications and two experimental units per plot, consisting of cowpea genotypes (‘Branquinho’ and ‘Sempre Verde’) and four forms of nutritional management (I - bacterial inoculation (B. japonicum, strains semia 5079 and semia 5080) in the seeds; N - nitrogen fertilization (urea); I + N - bacterial inoculant associated with nitrogen fertilization and T - Control, without seed inoculation and without nitrogen fertilization). Plant growth and production were evaluated, and the data were subjected to analysis of variance by the F test up to 5% probability and Tukey test (p<0.05). Of cowpea ’Branquinho’ expressed greater vegetative growth and greater production, and inoculation with B. japonicum in the seeds significantly increased the mass of 100 seeds of the Branquinho genotype, with an average of 22.29 g/100 seeds, which is equivalent to a percentage of 12.44% higher than the control. This result confirms an increase in production and seed size, constituting, therefore, an advantageous alternative for use by family farmers in Amapa, in addition to dispensing with nitrogen fertilization.